Effects of Spatial Speech Presentation on Listener Response Strategy for Talker-Identification - Uhrig, Stefan; Perkis, Andrew; Möller, Sebastian; Svensson, U. Peter; Behne, Dawn M. (Frontiers in Neuroscience, 2022)
This study investigates effects of spatial auditory cues on human listeners’ response strategy for identifying two alternately active talkers (“turn-taking” listening scenario). Previous research has demonstrated subjective benefits of audio spatialization with regard to speech intelligibility and talker identification effort. So far, the deliberate activation of specific perceptual and cognitive processes by listeners to optimize their task performance remained largely unexamined. Spoken sentences selected as stimuli were either clean or degraded due to background noise or bandpass filtering. Stimuli were presented via three horizontally positioned loudspeakers: In a non-spatial mode, both talkers were presented through a central loudspeaker; in a spatial mode, each talker was presented through the central or a talker-specific lateral loudspeaker. Participants identified talkers via speeded keypresses and afterwards provided subjective ratings. In the spatial mode, presentations at lateral loudspeaker locations entailed quicker behavioral responses, which were significantly slower in comparison to a talker-localization task. Under clean speech, response times globally increased in the spatial versus non-spatial mode (across all locations); these “response time switch costs”, presumably being caused by repeated switching of spatial auditory attention between different locations, diminished under degraded speech. No significant effects of spatialization on subjective ratings were found. These results suggested that when listeners could utilize task-relevant auditory cues about talker location, they continued to rely on voice recognition instead of localization of talker sound sources as primary response strategy. Besides, the presence of speech degradations may have led to increased cognitive control, which in turn compensated for incurring response time switch costs.